2018
DOI: 10.1007/s10067-018-4017-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of microRNA-132 and its target gene NAG-1 in evaluating therapeutic efficacy of non-steroidal anti-inflammatory drugs treatment in patients with ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is a common chronic rheumatic disorder, accompanied by the differential expression of various microRNAs (miRNAs) in patients suffering from the condition, some of which have the potential to serve as novel complementary AS biomarkers. During this study, AS patients were recruited in connection with our investigation into the correlation of microRNA-132 (miR-132) in peripheral blood and its target gene NAG-1 expressions in relation with the clinical efficacy of non-steroidal anti-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, recent studies on AS supported an increased expression of miR-29a in PBMCs (Huang et al 2019a, Yang et al 2019b. Ma et al (2016) found that miR-132 is downregulated in plasma; nevertheless, Guo et al (2018) showed that miR-132 is up-regulated in PBMCs (Ma et al 2016;Guo et al 2018). These divergent results may depend on the stages of AS, methods used, samples type (serum, plasma, PBMC, and whole blood) or the specific expression of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies on AS supported an increased expression of miR-29a in PBMCs (Huang et al 2019a, Yang et al 2019b. Ma et al (2016) found that miR-132 is downregulated in plasma; nevertheless, Guo et al (2018) showed that miR-132 is up-regulated in PBMCs (Ma et al 2016;Guo et al 2018). These divergent results may depend on the stages of AS, methods used, samples type (serum, plasma, PBMC, and whole blood) or the specific expression of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…And after full-text assessment, we eventually identified 29 articles that could be used for the systematic review of the miRNA expression profile. The full text of the 29 articles was assessed again in details, and nine of them (17)(18)(19)(20)(21)(22)(23)(24)(25) were included in our meta-analysis. A flowchart of the selection process of the articles is presented in Figure 1.…”
Section: Included Articlesmentioning
confidence: 99%
“…Some tried to use circulating miRNAs expression profiling as a diagnosis tool for AS but performance on validation cohorts still need to be assessed [54,57]. Few studies also tried to define the relation between miRNAs expression profile and treatment response in the perspective of using miRNAs as a therapeutic strategy tool but the process of validation has not been performed yet [66,67].…”
Section: B) Integration With Other -Omics Dataémentioning
confidence: 99%